Full-Bridge power resonant converter for the arcjet thruster of a small spacecraft - V. V. Fedyanin; V. V. Shalay; V. K. Fedorov; P. S. Yachmenev; I. S. Vavilov (Омский научный вестник)
In this paper, the applied problems of designing a bridge resonant converter with a high-voltage arc ignition system in the channel of an electric arc motor is solved. The development of a bridge resonant power supply is presented, a review and analysis of power sources of arcjet thruster of various capacities is carried out. The theoretical aspects of calculating the main parameters of the source are considered. The transfer function describing the gain of the resonant circuit of the power supply is given. With the help of the transfer function, gain diagrams are constructed for various values of the Q-factor of the contour. A prototype of a power supply, a starting system and an arcjet thruster is presented. A series of experiments aimed at identifying the operability of the source is carried out. According to the experimental results, the maximum output power of the source wiz 182,4 watts, and the maximum efficiency is 87,5 %. Frequency spectra of the output current of the power supply are obtained. The current-voltage characteristics for the Ar and N2 are constructed. In the course of the study, phenomena related to the chaotic dynamics of the arc in the engine channel are discovered. Chaotic fluctuations are observed at the moment of starting the engine and disappeared after steady-state operation.